Preferências políticas importam? : uma análise das sentenças criminais proferidas pelos juízes do Estado de São Paulo - Lucas Fernandes de Magalhães (2020)
Criminal proceedings in the first degree of jurisdiction usually end with a decision on the merits, that is, a sentence. If the decision is favorable to acquittal, the defendant does not receive any type of punishment. On the other hand, if the decision is condemnatory, a penalty is imposed on the defendant, as well as being assigned criminal status. What extra-legal factors influence the judge to position himself in favor of either outcome? The purpose of this dissertation is to answer this question. From an analysis of the main theories of the field of judicial behavior, the Attitudinal and Strategic Theories, we develop the central hypothesis of this research: the political preferences of judges affect their decisions, that is, punitive judges are more likely to deliver a condemnatory sentence than other judges. After developing a method to measure the political preferences of judges in the Guarantism-Punitivism dimension, we tested the hypothesis from an original database containing 487.664 criminal judgments handed down by São Paulo State Judges from 2013 to 2019. The statistically significant result was that with each increase of a unit in the estimated ideal point (towards a more punitive ideology) there is an increase of between 3.5% and 4.1% in the probability of the judge to deliver a condemnatory sentence, rather than an acquittal, corroborating the hypothesis raised. By way of illustration, in one of the models the judges whose ideals points were at ideological extremes were 54 units apart, meaning that the most punitive judge was approximately 2.89 to 3.21 times more likely to make a condemnatory sentence than the most guarantor judge.